Mengkonsumsi Cokelat Hitam Dapat Meningkatkan Magnesium Dalam Tubuh Dan Mengurangi Rasa Sakit Saat Menstruasi - Suci Ramadhani; Tri Yani (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2023)
Efforts to reduce pain in primary dysmenorrhea include using warm compresses, consuming analgesic medication, regular exercise, using aromatherapy, relaxing, drinking hot tea and dark chocolate (Rofiqoh, 2021:2). The content of dark chocolate such as caffeine, theobromine, methyl-xanthine, and phenylethylalanine is believed to improve mood and reduce fatigue so it can be used as a therapy to relieve primary dysmenorrhea because it has various ingredients that have anti-pain properties.